1983
DOI: 10.3109/10641968309048845
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Renin: A Possible Regulator of Aldosterone Production

Abstract: We have confirmed the presence of adrenal renin and have shown that the concentration is much higher in the glomerulosa cells. The renin concentration of these cells is influenced by changes in sodium balance and after nephrectomy, while the renin of the fasciculata-medullary tissue is not. There is a positive correlation between adrenal renin and aldosterone concentration. The data suggest that adrenal renin may be a local hormone that plays a role in the regulation of aldosterone production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0
1

Year Published

1984
1984
1995
1995

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 7 publications
4
30
0
1
Order By: Relevance
“…10 - 11 Recently, we showed that almost all of renin mRNA was in the adrenal zona glomerulosa with very little in the zona fasciculatareticularis and that the renin mRNA increased after sodium depletion in the rat. 17 These observations suggest that adrenal renin synthesized in glomerulosa cells may be a possible regulator of aldosterone secretion.…”
mentioning
confidence: 99%
“…10 - 11 Recently, we showed that almost all of renin mRNA was in the adrenal zona glomerulosa with very little in the zona fasciculatareticularis and that the renin mRNA increased after sodium depletion in the rat. 17 These observations suggest that adrenal renin synthesized in glomerulosa cells may be a possible regulator of aldosterone secretion.…”
mentioning
confidence: 99%
“…In the past decade, several studies conducted on animals found evidence for a complete RAS within various tissues, suggesting that locally generated Ang II may act as an autocrine or paracrine mediator that might be independently regulated from circulating RAS. 1 - 2 In the adrenals, local production of Ang II and angiotensin III (Ang III) may stimulate mineralocorticoid synthesis and secretion 3 and growth of adrenal cells 4 and may have an important role in the pathogenesis of high blood pressure, as suggested by studies on transgenic rats with high adrenal renin expression. 5 Many studies reported the presence of some RAS components in the adrenals of various animal species.…”
mentioning
confidence: 99%
“…On the other hand, recent biochemical and immunological studies revealed that renin exists in the adrenal gland of various mammalian species (1)(2)(3)(4)(5). It was also demonstrated that this adrenal renin is primarily located in the zona glomerulosa cells rather than the fasciculata or medullary cells (6,7). Further, the adrenal renin has been reported to increase markedly after high potassium loading or after nephrectomy (7)(8)(9), when plasma renin activity was at undetectable levels.…”
Section: Introductionmentioning
confidence: 99%